(untitled) (Marketing Journal, 2026)
This article examines the economic efficiency of implementing digital payment technologies in the activities of individual entrepreneurs (IEs) and self -employed persons. Analytical conclusions are presented on the impact of digital payments on reducing tra nsaction costs, increasing turnover and sales volumes, strengthening financial discipline and reporting, as well as expanding financial inclusion. The empirical basis of the study includes statistical data on payment infrastructure published by the Central Bank of the Republic of Uzbekistan, the World Bankʼs Global Findex database and financial inclusion reports, as well as open data and information released by government authorities. The article substantiates the role of digital payments in supporting sust ainable income generation in the segment of individual entrepreneurs and the self -employed, reducing the share of the shadow economy, and stabilizing state budget revenues.